The effect of the starting line-up of the players on the outcome of the set in Volleyball. - Laios, A; Kountouris, P; Laios, Y; S Drikos (11th International Conference of Sport Kinetics. 25–27 September 2009. Halkidiki, Greece., 2009)
THE EFFECT OF THE STARTING LINE-UP OF THE PLAYERS ON THE OUTCOME OF THE SET IN VOLLEYBALL. Laios. A.,  Kountouris. P.,  Laios. Y., Drikos. S. Faculty of Physical Education and Sport Science, University of Athens One of the peculiarities of the game of Volleyball is its rotation system. Before the beginning of every set the team coach must give to the referees in written form the starting positions of the six players of his team. During the set, every time the team wins a rally served by the opponent all its players shift their positions in a clockwise manner 1→6→5→4→3→2→1. During position shifts the relative positions of the players do not change. A complete rotation of the team is achieved after six position shifts, whence the players are again in the same positions as the starting line-up. After the application of the rally point system the number of rallies played per set (except the fifth one) was significantly reduced. The aim of the present study was to examine the distribution of the number of position shifts per set in various situations, with the intention to infer whether this information may prove to have practical importance. The primary data were collected from the Greek Men’s Volleyball Championship of 2005-2006 with the participation of twelve teams in a two round system. This gives a total of 132 matches, in which 491 sets were played. The primary dependent variable was the number of position shifts of the winning team. Its distribution was examined in different kinds of sets (first four or fifth) and in different outcomes of the set, measured as point differences between the winning and the losing team. For the first four sets the mean value of position shifts was 14.8±2.8 with only 6.8% of the sets having position shifts equal to or greater than 18. Even in the sets with a minimum difference between the two teams (25-23) and therefore a maximum number of points, the mean value of position shifts was 16.4±1.7 with only 9.1% of the sets having position shifts equal to or greater than 18. For the fifth set the mean value of position shifts was 9.0±2.3 with only 3.1% of the sets having position shifts equal to or greater than 12. Therefore the number of complete rotations for the first four sets was around two-and-a-half and the number of complete rotations for the fifth set was around one-and-a-half. In a previous research it was found that there seem to be favourable situations during position shifts, when the serving team has increased chances of winning the point. Since most probably during a set a team will not complete a whole number of complete rotations, the coach should start the set with the most favoured positions coming up first, or at least in the middle, but certainly not last. This will guarantee that the favoured positions will appear more frequently and most probably at crucial points at the end of the set. This is especially important in view of the fact that the winning team must win at least two more points than its opponent when serving, with the odds of winning against losing the rally when serving being only one to two.